Expanding access to finance to boost growth and reduce inequalities in Mexico - Maravalle, Alessandro (OECD Publishing, 2022)
The access to formal financial services in Mexico is particularly low. Access is also significantly unequal across income levels, gender, between rural and urban areas and across regions. SMEs access to bank credit is low, hampering firms' ability to grow and innovate. The use of cash and informal credit is still widespread, especially in rural areas, where financial infrastructure is underdeveloped. The diffusion of digital financial services is slowly advancing but remains low, hindered by a relatively low level of financial literacy and a digital divide. Expanding access to finance would enable Mexican households to invest in education and health, and better manage income shocks and smooth consumption. It would also enable Mexican firms to invest more, increase productivity and create formal jobs. Low-income households, small firms and more disadvantaged regions would particularly benefit, as it would unlock new economic opportunities for them. Boosting competition in the banking sector would facilitate SMEs access to credit by lowering interest rate margins. Upgrading the regulatory framework of the financial system would help increase competition and quality of financial services. The potential of the fintech sector is yet to be materialised, which would further increase competition and bring financial services to wider segments of the population. Strengthening financial education and digital literacy would facilitate a larger and better use of traditional and digital financial services
Keywords: Economics; Mexico